Black–White Achievement Differences and Governmental Interventions - Hanushek, Eric A (American Economic Review, 2001)
The estimates in the study considered whether any of the governmental or family factors individually could explain the magnitude and pattern of black-white achievement gaps. Neither the level nor the distribution of school spending appears to provide much explanation for the gaps. School spending levels show little consistent impact with any indication of differential impact on blacks being small. Direct analyses of the effects of spending equalization on performance similarly show little impact. On the other hand, governmental intervention through integration programs appears potentially more important.